2008
DOI: 10.3324/haematol.11897
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25+FOXP3+ T regulatory cells reconstitute and accumulate in the bone marrow of patients with multiple myeloma following allogeneic stem cell transplantation

Abstract: BackgroundVery little is known about the number and function of immunosuppressive CD4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 43 publications
6
46
0
Order By: Relevance
“…The finding that MM cells are able to induce the generation of Tregs in vitro further corroborates these results [61]. Furthermore, Tregs have been shown to expand and accumulate in the bone marrow of MM patients after allogeneic stem cell transplantation, and Tregs found in these patients are endowed with a strong inhibitory function, potentially inhibiting anti-myeloma immune control after transplantation [62].…”
Section: Regulatory/suppressive Cellssupporting
confidence: 72%
See 1 more Smart Citation
“…The finding that MM cells are able to induce the generation of Tregs in vitro further corroborates these results [61]. Furthermore, Tregs have been shown to expand and accumulate in the bone marrow of MM patients after allogeneic stem cell transplantation, and Tregs found in these patients are endowed with a strong inhibitory function, potentially inhibiting anti-myeloma immune control after transplantation [62].…”
Section: Regulatory/suppressive Cellssupporting
confidence: 72%
“…Highly suppressive Tregs expand and accumulate in the bone marrow after allo-SCT [62], and these cells might be able to convert into myeloma-promoting Th17 cells [25,85]. Murine studies suggest that combining allo-SCT with Id-or DC vaccination provides a possible solution to these issues [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that Tregs might contribute to the prevention of graft versus host disease via their immunosuppressive effect [18]. Similarly, high Treg populations were noted in the APBSCT (+) patients post surgery in the present study, suggesting that Tregs may play a role in stimulation of the immune system after APBSCT.…”
Section: Erçetin Et Al T Regulatory Cells In Multiple Myelomasupporting
confidence: 53%
“…As such, immunosuppressive CD4+CD25+FOXP3+ Tregs, PD-1, and CD200-a novel prognostic factor in MM-were selected as the subjects of the present study. CD4+CD25+FOXP3+ Tregs have a high level of expression in patients that undergo allogeneic bone marrow transplantation [18]. CD200 is also considered a novel prognostic factor in MM, with high expression [14].…”
Section: Introductionmentioning
confidence: 99%
“…17 We recently observed that after allo-SCT in myeloma patients, T-regulatory cells expanded faster than conventional CD4 þ cells in BM, and that they expressed mainly CD45RA( À )/CCR7( À ) memory-T-cell phenotype. 18 The number of studied patients and samples are too small to draw definite conclusions, but the figures suggest a rapid increase of activated T and NK cells 1-2 months after treatment, and a decrease of the activated T and NK cells after 3-4 months, whereas the major increase of Tregulatory cells was seen mainly after 6 months. This might be interpreted as a counter-regulatory reaction to the increase of activated T and NK cells.…”
Section: Discussionmentioning
confidence: 96%